Kajian Budaya Kontemporer - Arie Setyaningrum (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2002)
The old-positivistic approach to culture, which was insensitive to domination and inequality has been seriously challenged by new approaches: post stucturalis and post-colonialist. This article maps out and elaborates many ways of approaching culture in cultural studies.